Regression and correlation studies of some morphological traits in Tunisian orange (Citrus sinensis L) cv. Maltese Ballerin - El Bey, Naziha; Aounallah, Mohamed Karim; Sahli, Ali (International journal of Horticulture, Agriculture and Food science, 2020)
Citrus sinensis (L.osbeck) or sweet orange is an important fruit crop originated from South East Asia which is cultivated widely in tropical, subtropical and Mediterranean regions. It is consumed all over the world as an excellent antioxidant. The main objective of the present work is to identify various relationships in shoots and leaves of Tunisian sweet orange (Citrus sinensis L.) cv Maltese Ballerin. Significant relationships were obtained between primary and secondary growth (length and diameter of spring shoots), between the elongation and organogenesis (length, leaf number, node number) and between elongation and leaf area. Several non-destructive methods are proposed to estimate the leaf area, which is closely related firstly to the rectangle constructed from the length and width of the leaf (R2=0.9) and secondly to the leaf area obtained by the method of supervised classification using Envi software (R2=0.96). A significant linear relationship between the dry weight of the leaf and its area is found (R2=0.74).